Phytophthora Management for Commercial Citrus Groves - Megan M. Dewdney; Jamie D. Yates (EDIS)
PP269, a 2-page full-color fact sheet by Megan M. Dewdney and Jamie D. Yates, highlights symptoms and management for phytophthora foot rot, brown rot, phytophthora root rot, and diaprepes root weevil in citrus groves. Published by the UF Department of Plant Pathology, August 2009.